Relationship Self-Management Level of Hypertension Patients Towards Risk of Coronary Heart Disease - Pratiwi, Jiheny Siska; Rahayu, Sri (Poltekkes Kemenkes Tanjung Karang, 2024)
Most hypertension sufferers are not very strict in controlling themselves and managing their blood pressure to prevent complications. One of the significant risk factors for heart disease is hypertension. This study aims to ascertain if hypertension patients' degree of self-management and the prevalence of coronary heart disease are related. This specific type of research uses a cross-sectional study design and is quantitative. Purposive sampling is employed. The Slovin formula is used to compute the sample. The study's total sample was 109 outpatients with hypertension from the internal medicine polyclinic of Dr. Moewardi Surakarta Hospital. This study used the HSMBQ (Hypertension Self-Management Behavior Questionnaire) questionnaire by Nargis Akther to measure the level of self-management of hypertension with coronary heart disease. The data analysis used was a univariate test, and the risk level was calculated using the Framingham Risk Score and the chi-square bivariate test. Results show that the study's p-value=0.048 (<0.05) suggests a significant correlation between hypertension patients' degree of self-management and the prevalence of coronary heart disease. Most individuals fall into the category of having an adequate level of self-management. The majority of the 76 people (69.7%) with intermediate levels of self-management had a minor risk of coronary heart disease. The results of the study showed a significant relationship between the incidence of coronary heart disease and the level of self-control in hypertensive patients. Promotive and preventive efforts through educational approaches and structured interventions are essential to improve the quality of self-control in hypertensive patients.